Operational strategy for multi-converter based variable speed wind generator during network fault - Muyeen, S.M.; Tamura, J. (2011)
This paper proposes novel multiconverter operation and control scheme for variable speed wind energy conversion system to withstand against grid fault. The full or partial rating frequency converters (FCs), in general, are widely used in variable speed wind turbine (VSWT) driven wind generators. Among the variable speed wind generators, permanent magnet synchronous generator (PMSG), which uses a full rating FC for grid interfacing, is drawing much attention nowadays due to its salient features. However, considering the factors such as higher-reliability, higher efficiency, and lower harmonics, the multiconverter based topology might be preferable instead of using a full rating FC. This paper proposes a coordinated control scheme for multiple parallel-connected FC units integrated with VSWT driving PMSG to augments the transient performance during a network disturbance. Multimode operation (inverter and rectifier) of the individual FC unit is another salient feature of this study.